2009
DOI: 10.1016/j.ecoenv.2008.05.013
|View full text |Cite
|
Sign up to set email alerts
|

Ecological impacts of lead mining on Ozark streams: Toxicity of sediment and pore water

Abstract: a b s t r a c tWe studied the toxicity of sediments downstream of lead-zinc mining areas in southeast Missouri, using chronic sediment toxicity tests with the amphipod, Hyalella azteca, and pore-water toxicity tests with the daphnid, Ceriodaphnia dubia. Tests conducted in 2002 documented reduced survival of amphipods in stream sediments collected near mining areas and reduced survival and reproduction of daphnids in most pore waters tested. Additional amphipod tests conducted in 2004 documented significant tox… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
46
0
2

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 75 publications
(50 citation statements)
references
References 23 publications
2
46
0
2
Order By: Relevance
“…In all the experiments, the amount of the adsorbed metal, Nf, was determined by the difference between the initial concentration in aqueous solution and the concentration in the supernatant, according to Equation (1). (1) where N i represents the initial number of mols of metal in 50 mL of the solution, N s represents the number of mols of metal in the supernatant after stirring, and m is the Si-BP mass used in the experiment.…”
Section: Adsorption Experimentsmentioning
confidence: 99%
“…In all the experiments, the amount of the adsorbed metal, Nf, was determined by the difference between the initial concentration in aqueous solution and the concentration in the supernatant, according to Equation (1). (1) where N i represents the initial number of mols of metal in 50 mL of the solution, N s represents the number of mols of metal in the supernatant after stirring, and m is the Si-BP mass used in the experiment.…”
Section: Adsorption Experimentsmentioning
confidence: 99%
“…Sediment pollution by heavy metals has been regarded as a critical problem in marine environment because of their toxicity and bioaccumulation (Chapman et al, 1998;Islam and Tanaka, 2004;Singh et al, 2005;Todd et al, 2010). Many studies have shown that heavy metals in sediments could significantly impact the health of marine ecosystem (Snodgrass et al, 2008;Zheng et al, 2008;Besser et al, 2009). The toxicity and mobility of heavy metals in sediments vary greatly among different chemical forms (Perin et al, 1985;Cuong and Obbard, 2006;Fan et al, 2008;Yu et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Arsenic (As), cadmium (Cd), chromium (Cr), copper (Cu), nickel (Ni), lead (Pb) and zinc (Zn) are some of the most common heavy metal pollutants (Hakanson, 1980;Chen et al, 1991;Wong et al, 2001). These metals can enter estuaries and coastal waters through the discharge of industrial and municipal wastewaters, storm run-off, dust deposition, mine discharge, waste incineration, and other diffuse sources (Tanner et al, 2000;Dai et al, 2007;Meng et al, 2008;Zhang et al, 2008;Cheng et al, 2009;Besser et al, 2009;Cheng and Hu, 2010a,b;Hosono et al, 2010Hosono et al, , 2011. Sediment-bound heavy metals have a tendency to adsorb and accumulate on finegrained particles that eventually move into the depositional areas (Zhang et al, 2001;Morillo et al, 2002;Jain, 2004;Man et al, 2004;Qiu et al, 2005;Singh et al, 2005;Mendiguchía et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…The hot spots of heavy metal concentration are often near industrial plants [11]. Heavy metal emissions have been declining in some industrialized countries over the last few decades [12,13], however, anthropogenic sources have been increasing with rapid industrialization and urbanization in developing countries [14,15].Heavy metal contaminations in sediment could affect the water quality, the bioassimilation and bioaccumulation of metals in aquatic organisms, resulting in potential long-term affects on human health and ecosystem [16][17][18][19]. Quantification of the land-derived metal fluxes to the sea is therefore a key factor to ascertain at which extent those inputs can influence the natural biogeochemical processes of the elements in the marine [20,21].…”
Section: Introductionmentioning
confidence: 99%